Faktor demografis yang berhubungan dengan perilaku merokok pada remaja - Gani Apriningtyas Budiyati (STIKes Surya Global Yogyakarta, 2019)
Indonesia is one of the five largest cigarette consuming countries in the world. In addition, the data shows that the majority of smokers are the younger generation. Things that cause adolescents to smoke behavior can occur due to various factors, including smoking environment, gender, age, and other demographic factors. The aim of this study is to determine the relationship of demographic factors with smoking behavior in adolescents. This study used a cross sectional design. Respondents were vocational school adolescents. The population were 373 adolescents. The number of samples used in this study were 201 respondents. The sampling technique used simple random sampling. Data analysis used chi square test. Data collection used questionnaire. The results of bivariate analysis of the relationship between sex factors and smoking behavior have a significance value of 0,007 (p0,05) which means there was a relationship between sex and smoking behavior in adolescents. While other demographic factors such as age, parental education, pocket money, and status of residence did not show significant results (p0,05) which means there was no relationship between age, parental education, pocket money, and residence status with smoking behavior in adolescents. Conclusion of this study said that gender was a demographic factor associated with smoking behavior in adolescents.